Antimicrobial activities of some 5-(4-nitro aminophenyl)-l,2,4-triazoline-3-thione derivatives - (:unkn) unknown (My University, 1998)
We have synthesized 5-(4-nitro/aminophenyl)-1,2,4-triazoline-3-thione derivatives and screened them for their antibacterial, antifungal and antimycobacterial activities. We report the minimum inhibition concentration (MIC) values of compounds using the microdilution method. Some of the substances showed antimicrobial activity against some strains tested of bacteria and fungi. The results show that the amine derivatives were more active than the corresponding nitro derivatives. ©1998 Chapman & Hall Ltd.
Keywords: 5-(4-nitro/aminophenyl)-1,2,4-triazoline-3 thiones; Antibacterial agents; Antifungal activities; Antimycobacterial agents